Can the Newest Vital Sign Be Used to Assess Health Literacy in Children and Adolescents?. (February 2014) - Warsh, Joel; Chari, Roopa; Badaczewski, Adam; Hossain, Jobayer; Sharif, Iman
Context . We evaluated the validity of the Newest Vital Sign (NVS) as a brief screen for health literacy in children. Objectives . To ( a ) test the hypothesis that child performance on the NVS correlates with performance on a test of child reading comprehension and ( b ) establish age-based cutoffs for expected performance on the NVS. Design . Children aged 7 to 17 years were administered the NVS followed by the Gray Silent Reading Test (GSRT). Results . The NVS score correlated strongly with GSRT score (ρ = 0.71, P < .0001) and increased with age. Children aged 7 to 9 years had a median NVS score of 1 (interquartile range = 1-2); children aged 10 to 17 years had a median score of 3 (interquartile range = 2-4), P < .0001. Conclusion . The NVS performs well in this population. Children aged 10 to 17 years with an NVS score lower than 2 may have low health literacy.